Lignite as a natural active immobilization system for surface/drainage water polluted by fertilizers - Klučáková, Martina; Závodská, Petra; Pavlikova, Marcela; Bursik, Lukas; Sobotková, Veronika (Royal Society of Chemistry, 2025)
The quality of surface and drainage water is key for the health of nature; therefore, their contamination levels should be maintained under safe limits. This study focuses on water sampled from the & Rcaron;& iacute;& ccaron;ka tSream in the Czech Republic, which is contaminated mainly by nitrates and phosphates originating from fertilizers. Additionally, the content of heavy metals was monitored. The measured concentrations of Cd and Zn were below the limit of detection, while Cu and Pb remained below safe limits except during summer, likely due to the dry season. Concentrations of nitrates and phosphates exceeded the limiting values in all cases. Batch adsorption experiments using lignite were performed with both model solutions to determine adsorption capacity, which decreased in the order Pb > Cu > nitrates > phosphates. The experiments with real water samples from the & Rcaron;& iacute;& ccaron;ka Stream showed that lignite can effectively immobilize the studied pollutants. The adsorption efficiency was higher than 70% in all cases. The majority of the adsorbed pollutants remained in the immobilized forms both in the experiments with the model solutions and real water samples. An increased leachability was observed for nitrates; however, the equilibrium concentrations of nitrates after adsorption as well as their leachable form were under safe limits. Lignite can be considered an effective and low-cost adsorbent for the removal of pollutants from real water.
Keywords: lignite; immobilization; fertilizer; heavy metals